The prevalence and awareness of sleep apnea in patients suffering chronic pain: an assessment using the STOP-Bang sleep apnea questionnaire - Tentindo GS (Dove Medical Press, 2018)
Gregory S Tentindo,1 Scott M Fishman,2 Chin-Shang Li,3 Qinlu Wang,4 Steven D Brass5,6 1Department of Oral and Maxillofacial Surgery, University of California San Francisco, San Francisco, CA, USA; 2Department of Anesthesiology, Division of Pain Medicine, University of California Davis, Sacramento, CA, USA; 3Department of Public Health Sciences, Division of Biostatistics, University of California Davis, Sacramento, CA, USA; 4Department of Statistics, University of California Davis, Davis, CA, USA; 5Department of Neurology, University of California Davis, Sacramento, CA, USA; 6Department of Administration, Providence Little Company of Mary Medical Center San Pedro, San Pedro, CA, USA Purpose: Some patient subsets are at higher risk of sleep apnea, including patients with chronic pain. However, it is unclear whether patients and their caregivers are aware of the possibly increased risk of sleep apnea in this population. Chronic pain is often treated with opioids which may decrease both the central respiratory drive and the patency of the upper airway, potentially contributing to this sleep disorder. Using a self-reporting questionnaire approach in the chronic pain population, this study surveyed patient and caregiver awareness surrounding the risk of sleep apnea. In addition, we looked at the influence of opioid therapy on the prevalence of sleep apnea. Participants and methods: Consecutive patients presenting to a pain clinic were invited to participate anonymously in a survey that included the STOP-Bang sleep apnea questionnaire, which assesses patients’ knowledge, testing, diagnosis, or treatment of sleep apnea and whether their caregivers had discussed with them their increased risk of sleep apnea and opioid use. Results: Among 305 participating patients, 58.2% (n=173) screened positive for sleep apnea. Among the 202 patients on opioid therapy, 59.2% (116/202) were STOP-Bang positive (score ≥3). However, only 37.5% (n=72/173) of these patients had discussed their risk of sleep apnea with a caregiver and only 30.7% (n=59) underwent testing. Against expectation, opioids did not increase the prevalence of sleep apnea in our study population. Conclusion: Chronic pain patients had a high risk of sleep apnea, regardless of opioid prescription. Most patients were unaware of their increased risk and denied undergoing the necessary testing. Greater attention to screening, testing, and education for sleep apnea needs to be paid in chronic pain patients, especially given the potentially dangerous ramifications of opioid-induced sleep apnea. Keywords: sleep apnea, opioids, narcotics, STOP-Bang survey